2015
DOI: 10.1636/j14-48.1
|View full text |Cite
|
Sign up to set email alerts
|

Predator cues have contrasting effects on lifespan ofPardosa milvina(Araneae: Lycosidae)

Abstract: Predators can affect prey indirectly by eliciting changes in behavior, morphology, and life history. These nonconsumptive effects are often mediated by predator cues used by prey to avoid capture. However, predator cues can cause stress responses in prey that negatively impact survival and reproduction. We explored responses of the wolf spider Pardosa milvina (Hentz 1844) to cues from the larger wolf spider Tigrosa helluo (Walckenaer 1837) and the ground beetle Scarites quadriceps Chaudoir 1843. We exposed Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
1
8
1
Order By: Relevance
“…In a previous study significant reduction in the longevity of prey was sexually dimorphic when exposed to cues from the predaor . When the spider Pardosa milvina (Hentz 1844) was exposed to predators cues from the larger wolf spider Tigrosa helluo (Walckenaer 1837), P. milvina females had significantly shorter lifespans than those spiders without predator cues . However, in our study a sexually dimorphic response was only observed in the longevity of male A. limonicus exposed to ant odour, despite a lack of impact on the development and survival rates.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…In a previous study significant reduction in the longevity of prey was sexually dimorphic when exposed to cues from the predaor . When the spider Pardosa milvina (Hentz 1844) was exposed to predators cues from the larger wolf spider Tigrosa helluo (Walckenaer 1837), P. milvina females had significantly shorter lifespans than those spiders without predator cues . However, in our study a sexually dimorphic response was only observed in the longevity of male A. limonicus exposed to ant odour, despite a lack of impact on the development and survival rates.…”
Section: Discussioncontrasting
confidence: 64%
“…In a previous study significant reduction in the longevity of prey was sexually dimorphic when exposed to cues from the predaor . When the spider Pardosa milvina (Hentz 1844) was exposed to predators cues from the larger wolf spider Tigrosa helluo (Walckenaer 1837), P. milvina females had significantly shorter lifespans than those spiders without predator cues .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Shifts in insect prey traits in response to predators include behavioral changes [7][8][9][10][11], life history adjustments [12][13][14], and physiological changes [15][16][17][18][19] (See Table 1 & 2 for behavioral and physiological changes, respectively). The majority of studies to date link NCEs to changes in behavior, including changes in feeding [20][21][22], oviposition [23,24], colonization or dispersal [25][26][27], host-plant preference or habitat use [28][29][30] and increased predator avoidance [31,32].…”
Section: Insect Responses To Predation Riskmentioning
confidence: 99%
“…Decreases in litter complexity may also be associated with increases in cannibalism and/or intraguild predation due to both a lack of refugia and a loss of alternative prey (Wagner and Wise, 1996) but reduced prey also can increase exploitative competition among ground spiders (Wise and Wagner, 1991). At least within agricultural systems, there is evidence that ground beetles and ground spiders can have nonconsumptive effects on lifespan and behavior mediated by cues from intraguild predators (Sitvarin 2014;Sitvarin, Breen, and Rypstra 2015;Sitvarin et al 2016;Sitvarin and Rysptra 2014).…”
Section: Discussionmentioning
confidence: 99%